Role of Technical Knowledge and Family Socio-economic Status on Occupational Attainment of Vocational High School (SMK) Graduates - Pratama, Muhammad Rizki (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
This research seeks to conduct studies related to the level of occupational attainment of vocational graduates correlated with the level of technical knowledge and family socio-economic status in Sidoarjo Regency. The sample taken was 100 respondents with the criteria of having graduated from SMK for more than 3 years and having worked or had worked. This study produces several results. First, technical knowledge and family socio-economic status have a significant correlation with occupational attainment of vocational school graduates. Second, occupational aspirations have a significant contribution in strengthening the previous two correlations. This result suggests that the level of technical knowledge and family socio-economic status remain the main variables contributing to the level of occupational attainment. However, the level of occupational aspirations is an important factor to develop in order to stimulate better occupational attainment.